Effect of Hf doping content on the structure, optical and electrical properties of flexible HfxZn1-xO thin films by sol-gel method. (January 2021) - Peng, Qianwen; Duan, Libing; Shen, Hao; Wang, Di; Han, Cong; Niu, Yanfen; Zhao, Xiaoru
Abstract: Transparent and conducting Hf x Zn1- x O thin films with nominal Hf doping concentration ( x = 0–7%) were successfully synthesized on flexible polyimide (PI) substrates by the sol-gel spin coating method. All films showed hexagonal wurtzite structure of ZnO with preferred orientation of c -axis after air and vacuum annealing. The minimum resistivity reached to as low as 6.3 × 10 -2 Ω cm after annealed in vacuum atmosphere with 3% Hf content. The carrier concentration increased from 10 18 cm -3 to 10 19 cm -3, while Hall mobility decreased from 23 cm 2 v -1 s -1 to 3 cm 2 v -1 s -1 with increasing Hf concentration. According to the SEM and XPS analysis, for x = 0–3%, grain boundary scattering was the major factor of mobility, while for x = 5–7%, besides the grain boundary scattering, ionized impurity and natural scattering also play a crucial role in the variation of mobility. The minimum resistivity was due to the competition of increasing carrier concentration and decreasing mobility.